TECHNOLOGIES WITH OZONE IN HEMODIALYSIS: INNOVATION AND SUSTAINABILITY - Inês de Oliveira Silva Vaccari, Maria (Health and Society, 2024)
This study aimed to verifying the impacts of technologies with ozone in water treatment and disinfection of hemodialysis water systems, replacing the conventional chemical processes. Through scientific research developed on the subject, the study conducted a comparative analysis between the conventional technologies and technologies using ozone, in order to evaluate positive aspects and fragilities; and demonstrate it’s contribution to the practice of sustainability in economic, social and environmental aspects. The results of these analyzes demonstrated that the technologies with ozone are a safe and effective method, which results in the improvement of hemodialysis; giving quality and sustainability to the process.